Pengaruh Non Performing Loan (NPL) dan Biaya Operasional Pendapatan Operasional (BOPO) terhadap Return On Asset (ROA) pada Bank BUMN Periode 2014-2020 - Pramudya, Bagas Ardhi; Kusumah, R. Wedi Rusmawan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to study how non-performing loans (NPL) and operational costs affect the return on assets (ROA) of state-owned banks. Corporate banking from all companies was sampled from four state-owned institutions: Bank Mandiri Tbk, Bank Rakyat Indonesia Tbk, Bank Negara Indonesia Tbk, and Bank Tabungan Negara Tbk. The method used in this research is a quantitative method. The data used to create this visualization is taken from the annual report submitted by the Indonesian Stock Exchange's Financial and Trade Regulatory Agency. The data in this study were analyzed using SPSS, which carried out various tests and statistical analysis, including descriptive analysis, the classical assumption test, multiple regression analysis, and the t test. The results of this study show that non-performing loans (NPLs) have a negative impact on BUMN banking ROA with large margins from 2014 to 2020. This indicates that when non-performing loans (NPL) increase, the return on assets (ROA) decreases, and vice versa. The impact of state-owned banking operational costs on return on assets (ROA) between 2014 and 2020 is negative and substantial. Simply put, the higher the BOPO, the greater the ROA.